From the charge conditions and internal short-circuit strategy to analyze and improve the overcharge safety of LiCoO2/graphite batteries. (20th August 2018) - Deng, Yaoming; Ma, Zhen; Song, Xiaona; Cai, Zhuodi; Pang, Peipei; Wang, Zheng; Zeng, Ronghua; Shu, Dong; Nan, Junmin
Abstract: The overcharge safety and behaviors of lithium-ion batteries (LIBs) with LiCoO2 cathode are investigated under a successive constant current (CC) and constant voltage (CV) charge mode. It is indicated that in the case of smaller charge currents, a higher probability for the LIBs passing the overcharging test can be obtained. The batteries can safely pass CC overcharge test at 0.25C to 10 V, and then about 80% batteries can also pass CV overcharge test. Whereas, with increasing the CC currents to 0.33C, 0.5C, and 1C, about 50%, 30%, and 10% batteries can directly pass the overcharge test at the CC step, and then about 20%, 10%, and 0% batteries approach 10 V and subsequent pass CV overcharge test, respectively. Besides the charge current, it is also demonstrated that whether the LiCoO2 /graphite batteries are likely to achieve energy balance and pass the overcharge test basically depends on the formation of the internal short-circuit pathways derived from the cobalt and lithium deposition in the separator during the overcharge process. The cobalt deposition will be more uniform when the battery core has shape stability of assembly-structure, which can be used as an effective measure to raise LIBs through the overcharge test. In addition, relative more uniform cobalt dendrites can also be formed if a double layer separator is adopted, which reduces the local short-circuit risk caused by the melting or shrinkage of the separator and correspondingly improves the ratio of LIBs passing through the overcharge test. These risk reduction measures can be used in the battery manufacture to improve the overcharge safety of LIBs.